Evaluation Study of Distance Learning Program for Indonesian Migrant Children Using Context, Input, Process, Product (CIPP) Method in Indonesian School of Kota Kinabalu - Asdar, Muh; Hardiman, Fransisco Budi (UNDIKMA, 2023)
The Distance Open Learning (TJJ) program is an education program that offers ease of learning by utilizing information and communication technology (ICT). This TJJ program aims to expand and facilitate access to education for children of Indonesian migrant workers (PMI) in Sabah who are constrained and unable to get education through regular program Indonesian School of Kota Kinabalu. This research aims to evaluate the implementation of the TJJ Program at Indonesian School of Kota Kinabalu (SIKK) using the CIPP (Context, Input, Process, Product) research model. This research uses qualitative and quantitative approaches with an evaluation study method. Respondents in this research amounted to 113 students. The results of the evaluation of the SMA TJJ SIKK program based on the evaluation of a) Context, has the ability to implement programs with goals in line with the vision and mission of the school, but still needs improvement so that the program targets can be achieved as a whole b) Input, needs attention to learning models, costs and other supporters to be better and more appropriate, c) Process, needs improvement in terms of learning technology, interactive materials and communication media used, d) Product, the results of the program are in accordance with the objectives to be achieved, namely increasing the ability and opportunity to access education for PMI children.